300 NASAL CARRIAGE OF POTENTIALLY VIRULENT STRAINS OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS AMONG OTHERWISE HEALTHY CHILDREN IN MOBILE, ALABAMA. (1st January 2005) - Smith, K. A.; Plano, L.; Estrada, B.
Abstract : Purpose: To evaluate the rate of nasal carriage of methicillin-resistant Staphylococcus aureus (MRSA) in healthy children and to determine the staphylococcal chromosomal cassette mec (SCCmec) type and toxin profile of these isolates. Methods: Nasal swabs were obtained from children 0-18 years old during their well-child visits at the University of South Alabama outpatient pediatric clinic. All samples were collected during April of 2004. S. aureus was isolated with selective media and antibiotic susceptibilities were performed utilizing the Kirby-Bauer method. D-test was performed among all MRSA isolates resistant to erythromycin. SCCmec type was determined for all MRSA isolates using a multiplex PCR technique. All MRSA and available MSSA isolates were screened for the presence of selected toxin genes using PCR with oligonucleotides specific for the toxins of interest. These toxins included Panton-Valentine leukocidin (PVL), leukocidins LukD-E and LukM, staphylococcal toxic shock syndrome toxin (TSST), and the exfoliative toxins ETA and ETB. Results: Nasal cultures were obtained from 100 children. MRSA was isolated from the nares of 8% of study subjects while methicillin-susceptible strains of S. aureus (MSSA) were isolated from 23%. 32 children had family members who were health care workers (HCW) and 21 children attended day care centers. None of the cultures from children within these two groups yielded MRSA. Six (75%) of the MRSA isolates were resistant to erythromycin, none of which was resistant to clindamycin. All MRSA isolates were found to be SCCmec type IV. Toxin gene profiles were performed on all MRSA and 13 available MSSA isolates. A high rate of carriage for the gene encoding PVL and the other leukocidins was observed with all isolates. TSST and ETB but not ETA were detected in both MRSA and MSSA isolates. Conclusion: There is a high rate of nasal colonization with MRSA among healthy children in our population. The MRSA SCCmec type IV fits the profile associated with community-associated MRSA strains observed elsewhere. Most of the MRSA strains carry PVL and there are associations with TSST and ETB, which suggests a potential for virulence. Day care attendance and contact with HCW are not associated with nasal carriage of MRSA among the children included in this study.